2017
DOI: 10.1016/j.postharvbio.2017.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pulsed electric fields on the antioxidant potential of apples stored at different temperatures

Abstract: Està subjecte a una llicència de Reconeixement-NoComercial-SenseObraDerivada 4.0 de Creative Commons Effect of pulsed electric fields on the antioxidant potential of apples stored at different temperatures

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 30 publications
1
15
0
1
Order By: Relevance
“…Although the increase in the carotenoid content in the derived product obtained from PEF-treated tomatoes may be difficult to explain due to the complexity of biological systems, a wellestablished explanation for this observation is the activation of the secondary metabolism in the fruit as a strategy to overcome unfavourable conditions. 11,23,26 The significant correlation found between lycopene and its precursors, phytoene and phytofluene ( p < 0.0001; r = 0.7612 and r = 0.7661, respectively), have led us to hypothesize that PEF treatments may activate the transcription of genes encoding enzymes such as phytoene synthase (SIPSY) and carotenoid isomerase enzyme (CRTISO), responsible for the biosynthesis of these carotenoids in the fruit, as previously suggested by Vallverdú-Queralt et al (2013). 10 After lycopene, the carotenoid biosynthetic pathway is divided into two branches.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the increase in the carotenoid content in the derived product obtained from PEF-treated tomatoes may be difficult to explain due to the complexity of biological systems, a wellestablished explanation for this observation is the activation of the secondary metabolism in the fruit as a strategy to overcome unfavourable conditions. 11,23,26 The significant correlation found between lycopene and its precursors, phytoene and phytofluene ( p < 0.0001; r = 0.7612 and r = 0.7661, respectively), have led us to hypothesize that PEF treatments may activate the transcription of genes encoding enzymes such as phytoene synthase (SIPSY) and carotenoid isomerase enzyme (CRTISO), responsible for the biosynthesis of these carotenoids in the fruit, as previously suggested by Vallverdú-Queralt et al (2013). 10 After lycopene, the carotenoid biosynthetic pathway is divided into two branches.…”
Section: Resultsmentioning
confidence: 99%
“…According to previous studies, different electric field strengths (0.4, 1.2 and 2 kV cm −1 ) and number of pulses (5, 18 and 30 pulses) were applied at a low frequency of 0.1 Hz. The specific energy input corresponding to each treatment was calculated according to Soliva-Fortuny et al (2017) 23 and is displayed in Table 1. Each PEF treatment was repeated twice.…”
Section: Pulsed Electric Field Treatmentsmentioning
confidence: 99%
“…Isomerization and oxidation that occurred during the thermal treatment resulted in the degradation of antioxidants. According to Soliva‐Fortuny et al ., PEF treatment (0.008 kJ kg −1 ) of apple preceding drying enhanced the TPC and TFC compared to the untreated apple slices.…”
Section: Emerging and Innovative Ntp Technologymentioning
confidence: 98%
“…In this sense, increased total phenolic content has been described in tomato treated at 1.2 kV cm -1 (Vallverdú-Queralt et al, 2012) and apple treated at 1.85 kV cm -1 (Wiktor et al, 2015). Soliva-Fortuny et al (2017) explored the effects of different PEF intensities, as well as time and temperature after treatment, on the phenolic content of apple fruits. These authors reported 13%, 92% and 67% increases in the total phenolic, total flavan-3-ol contents and antioxidant capacity (respectively) in apples treated at 0.01 kJ kg -1 and stored for 24 h at 22 °C, although possible effects on individual phenolic compounds and apple quality attributes were not evaluated.…”
Section: Accepted Manuscriptmentioning
confidence: 99%